Effect of menopausal hormone therapy on components of the metabolic syndrome. (January 2017) - Lovre, Dragana; Lindsey, Sarah H.; Mauvais-Jarvis, Franck
The world population is aging, and women will spend an increasing share of their lives in a postmenopausal state that predisposes to metabolic dysfunction. Thus, the prevalence of metabolic syndrome (MetS) in women is likely to increase dramatically. This article summarizes the effects of menopause in predisposing to components of MetS including visceral obesity, dyslipidemia, type 2 diabetes (T2D) and hypertension (HTN). We also summarize the effects of menopausal hormone therapy (MHT) in reversing these metabolic alterations and discuss therapeutic advances of novel menopausal treatment on metabolic function.